Manajemen Event Dalam Penguatan Branding Kota Wisata dan Budaya - Marta, Revi; Hafivi, Ilham; Diego, Diego; Trianto, Indra (Jurnal Pustaka Komunikasi, 2024)
Entertainment is a human need fulfilled through tourism, which not only provides enjoyment but also offers new experiences. The tourism sector has significant potential to boost local and national economies, requiring effective management and promotion through various strategies, including events. This research highlights the crucial role of event management in strengthening the branding of Sawahlunto City as a "Cultural Mining Tourism City," focusing on how events can be designed, managed, and evaluated to support the city's identity. This study employs a qualitative approach with a case study method. The results showed that the event management was still far from what should be done. This can be seen from several points that are not well implemented in the procurement of the event.Research that is seen from the shortcomings related to preliminary research that should be done before event planning. Design that has been done quite well by the city government of Sawahlunto. Planning is seen from the city government of Sawahlunto has been in accordance with what should be related to event planning to brand the city. Coordination is seen that the Sawahlunto city government pays less attention to this. And evaluation is not done by the city government of Sawahlunto.